I wish I were a butterfly - Howe, James, 1946-; Young, Ed (San Diego : Harcourt Brace Jovanovich, 1987)
A wise dragonfly helps a despondent cricket realize that he is special in his own way.
"Gulliver books."
Keywords: Friendship -- Fiction; Self-acceptance -- Fiction; Crickets -- Fiction; Dragonflies -- Fiction